2010
DOI: 10.1097/mao.0b013e3181edb8b2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hearing Preservation After Microsurgical Excision of Vestibular Schwannoma

Abstract: Objective To examine long-term hearing outcomes after microsurgical excision of vestibular schwannoma (VS). Study Design Retrospective case review. Setting Tertiary referral center. Patients Forty-nine subjects at a single institution who had undergone microsurgical excision of a VS via middle cranial fossa (MCF) approach between 1994 and 2007 with immediate postoperative (PO) hearing preservation and for whom long-term audiograms were available. Intervention Diagnostic. Main Outcome Measures Word Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 36 publications
(56 reference statements)
3
52
0
1
Order By: Relevance
“…Speech discrimination is affected disproportionately with atrophy of the cochlear nerve (1820); thus, a purely retrocochlear mechanism of hearing loss would mean that pure tone threshold shifts would almost always be accompanied by severe decrement in speech discrimination. Clinical experience has clearly shown that many patients with VS have relative preservation of speech discrimination along with pure tone hearing loss (2327). Therefore, it is logical to conclude that cochlear pathology of the type observed in this study contributes to the pure tone threshold shifts in VS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech discrimination is affected disproportionately with atrophy of the cochlear nerve (1820); thus, a purely retrocochlear mechanism of hearing loss would mean that pure tone threshold shifts would almost always be accompanied by severe decrement in speech discrimination. Clinical experience has clearly shown that many patients with VS have relative preservation of speech discrimination along with pure tone hearing loss (2327). Therefore, it is logical to conclude that cochlear pathology of the type observed in this study contributes to the pure tone threshold shifts in VS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that over 80% of cochlear neurons have to be lost before there is a significant shift in pure tone thresholds, and that such severe neuronal losses are associated with a severe drop in speech discrimination ability (21,22). Clinical data has demonstrated the occurrence of mild to moderate degrees of threshold shift with relatively preserved speech discrimination in patients with a VS: analysis of data pooled from 5 published studies (2327) showed that a speech discrimination score (SDS) of > 65% was found in all patients (100%) with a preoperative pure tone average (PTA) between 20 – 40 dB HL, in 68% of the patients with a PTA between 40 – 60 dB HL, and in 50% with a PTA between 60 – 80 dB HL. Clinical studies have also shown that hearing loss does not correlate with the size of VS (28,29), indicating that compression of the cochlear nerve within the internal auditory canal may not be the only mechanism in hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Additional advantages of such a system are that this classification divides the postoperative results into 6 separate categories, which facilitates differentiation of the outcomes. Moreover, this system places relatively less importance on PTA in relation to the SDS, which serves as a more accurate predictor of the patients that could benefit from hearing aids [Meyer et al, 2006;Woodson et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Our newly designed intracranial electrode enables continuous and reliable auditory monitoring by use of cochlear nerve compound action potentials (CNAPs). 49,51,54 We report long-term outcomes of curative tumor removal with preservation of hearing and facial function; thus, we recommend that tumor removal be the first-line management strategy for younger patients with small ANs and preserved hearing.…”
mentioning
confidence: 94%